Evaluation of Complications of Intra-Prostatic Local Anaesthesia and Periprostatic Local Anaesthesia for Trus Guided Prostate Biopsy - choudhury, Am Anamur Rashid; Islam, Md Waliul; Chowdhury, Md Golam Mowla; Parveen, Tasmina; sultana, Parveen (Bangladesh Journal of Urology, 2020)
Objectives : To evaluate complications in Intra-prostatic local Anaesthesia and Periprostatic local Anaesthesia for TRUS Guided Prostate Biopsy. Methods: This study was carried out in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Medical College (DMCH) and Comfort Nursing Home, Dhaka during the period of January 2009 to October 2009, evaluate complications between periprostatic with intraprostatic local anaesthesia for transrectal prostate biopsy. For this purpose, a total number of 60 consecutive patients having increased prostate specific antigen (PSA >4.0ng/ml), abnormal DRE/transrectal ultrasound were admitted in the above mentioned hospitals were enrolled in this study for surgical management. Result : The age ranged from 50 to 90 years and the maximum number was found in the age group of 61-70 years in both groups. The mean(±SD) age was 68.5±7.5 years and 70.3±8.2 years in group I and group II respectively. No systemic lidocaine toxicity was observed in group II. But only dizziness were found in 2 cases (6.7%) and visual disturbance were found in 1 (3.3%) case respectively in group I. Urinary tract infection was found 2(6.7%) in group I and 1(3.3%) in group II patients. Hematuria was found 23(76.7%) in group I and 19(63.3%) in group II. Rectal bleeding was found 14(46.7%) in group I and 11(36.7%) in group II. The statistically not significant (p>0.05) between two groups in chi square and fisher exact test respectively. Conclusion : It is a simple and safe method that is less painful and it should be considered in all patients undergoing transrectal ultrasound guided prostate biopsy. Complications wer4e less in intra-prostatic local anaesthesia than periprostatic local anaesthesia for TRUS guided prostate Biopsy. Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.82-86